enter image description here

I'm having trouble proving that all the white and green areas have the same area, from there on we can obtain the answer $1+\sqrt5$ by proving that the inner red triangle points are midpoints.


There is also the following way (Guy Rawe found).

Since $QD||PC$, $FP||BR$ and $RE||AQ,$ we obtain: $$\frac{QR}{RC}=\frac{QD}{PC}=\frac{BQ}{BP}=\frac{BQ}{BQ+PQ}=\frac{1}{1+\frac{PQ}{BQ}}=\frac{1}{1+\frac{FQ}{QR}}=\frac{QR}{QR+FQ}=\frac{QR}{FR},$$ which gives $$RC=FR.$$

Similarly, we obtain: $$AP=PD,$$ $$BQ=QE$$ and the rest is smooth.

Why does $QD||PC?$

Because $$S_{\Delta PQC}=S_{\Delta PQR}+S_{\Delta PRC}=1+S_{\Delta PRC}=S_{\Delta CDR}+S_{\Delta PRC}=S_{\Delta PDC}.$$

  • $\begingroup$ how do we know that those lines are parallel? $\endgroup$ – SuperMage1 Jul 13 at 15:08
  • $\begingroup$ @SuperMage1 I added something. See now. $\endgroup$ – Michael Rozenberg Jul 13 at 15:16

Let $AD$, $BE$ and $CF$ be our chevians of $\Delta ABC$.

Also, let $AD\cap BE=\{P\}$, $AD\cap CF=\{R\}$ and $BE\cap CF=\{Q\}.$

Thus, $$S_{\Delta APE}=S_{\Delta BQF}=S_{\Delta CRD}=S_{\Delta PQR}=1.$$ Let $S_{AFQP}=x,$ $S_{BDRQ}=y$ and $S_{CEPR}=z$.

Thus, $$S_{\Delta BDR}=\frac{S_{\Delta BDR}}{S_{\Delta CDR}}=\frac{BD}{DC}=\frac{x+y+2}{z+2},$$ which gives $$S_{\Delta BQR}=y-\frac{x+y+2}{z+2}=\frac{yz+y-x-2}{z+2}.$$ Now, $$S_{\Delta AFQ}=\frac{S_{\Delta AFQ}}{S_{\Delta BFQ}}=\frac{AF}{BF}=\frac{x+z+2}{y+2},$$ which gives $$S_{\Delta AQP}=x-\frac{x+z+2}{y+2}=\frac{xy+x-z-2}{y+2}.$$ Thus, $$\frac{\frac{x+z+2}{y+2}+1}{\frac{xy+x+z-2}{y+2}}=\frac{S_{\Delta AFQ}+S_{\Delta BQF}}{S_{\Delta AQP}}=\frac{S_{\Delta ABQ}}{S_{\Delta AQP}}=$$ $$=\frac{BQ}{PQ}=\frac{S_{\Delta BQR}}{S_{\Delta PQR}}=S_{\Delta BQR}=\frac{yz+y-x-2}{z+2}.$$ Id est, $$\frac{x+y+z+4}{xy+x-z-2}=\frac{yz+y-x-2}{z+2}$$ or $$(y+1)(z^2+x^2-xy+2x+4z-xyz+4)=0,$$ which gives $$z^2+x^2-xy+2x+4z=xyz-4.$$ By the same way we can obtain: $$x^2+y^2-yz+2y+4x=xyz-4$$ and $$y^2+z^2-zx+2z+4y=xyz-4.$$ Now, let $x=\max\{x,y,z\}$.

Thus, $$x^2+y^2-yz+2y+4x-(y^2+z^2-zx+2z+4y)=0$$ or $$(x-z)(x+z)+z(x-y)+4x-2y-2z=0$$ or $$(x-z)(x+z+2)+(x-y)(z+2)=0,$$ which gives $$x=y=z,$$ $$x^2+6x=x^3-4$$ or $$x^3-x^2-6x-4=0$$ or $$x^3+x^2-2x^2-2x-4x-4=0$$ or $$(x+1)(x^2-2x-4)=0$$ or $$x=1+\sqrt5$$ and we are done!


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.